1989
DOI: 10.1139/b89-230
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of achene characteristics within and among diploid and tetraploid clones of Solidago flexicaulis and their significance in germination and resource allocation studies

Abstract: Achene characteristics were examined within clones, among clones of a cytotype, and between the diploid and tetraploid cytotypes of Solidago flexicaulis. The pattern of intraclonal variation was similar in each of the three diploid and five tetraploid clones. In each of the clones, embryo weight increased with increasing achene weight and the number of days taken to germinate increased with increasing pericarp weight. Other significant correlations were not consistent among all clones. Generally, clones of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
3
3
0
Order By: Relevance
“…The independence of germination time and achene weight for tetraploid A. pilosus var. pilosus is in agreement with the results presented by Chmielewski (1991) for the cytotypes of A. lanceolatus. It is worth noting, however, that McEvoy (1984) found that germination time in Senecio jacobaea decreased with increasing achene weight in disk achenes, but increased with increasing achene weight in ray achenes.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The independence of germination time and achene weight for tetraploid A. pilosus var. pilosus is in agreement with the results presented by Chmielewski (1991) for the cytotypes of A. lanceolatus. It is worth noting, however, that McEvoy (1984) found that germination time in Senecio jacobaea decreased with increasing achene weight in disk achenes, but increased with increasing achene weight in ray achenes.…”
Section: Discussionsupporting
confidence: 93%
“…The increased likelihood of germination as a consequence of increased achene weight is not a unique feature ofthis species or genus. Similar results have been reported within the tribe for both Aster acuminatus (Pitelka, Thayer, and Hansen, 1983) and A. lanceolatus (Chmielewski, 1991), Seneciojacobaea L. (McEvoy, 1984), and Solidago flexicaulis L. (Chmielewski et aI., 1989).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Seed heteromorphism may occur at the level of the inflorescence (Cavers and Steel, 1984;Venable et al, 1995), individual (McGinley, 1989;Sakai and Sakai, 1996;Chmielewski, 1999), clone (Chmielewski et al, 1989), population (Venable et al, 1995) or species (Maun and Payne, 1989;Walck et al, 1997). Morphological heteromorphism may occur in seed size (Maun and Payne, 1989), seed shape (Venable and Burquez, 1989), seed colour (McGinley, 1989;Doucet and Cavers, 1997;Puga-Hermida et al, 2003a) (Fig.…”
Section: Heterogeneity In Wild Seedsmentioning
confidence: 99%